Tribological Behaviour of Bio-lubricants for Machinery using a Four-ball Tribotester - Abdullah, Muhammad Haiqal; Ibrahim, Siti Aida (Progress in Engineering Application and Technology, 2021)
The world’s oil reserves are depleting, and the effort to reduce the dependency on mineral oil-based products has been carried out since the late 90s. The pursue of bio-lubricants made of vegetable and animal fats has become the top candidates as the base of the alternative bio-lubricant. However, for the bio-lubricant to be used in the industrial machinery sector, it needs to be tested for its tribological properties (coefficient of friction, wear scar diameter, flash temperature parameter, worn scar diameter). To ensure that the compound is suitable for machinery since machinery consists of smaller parts that function together. The most suitable test machine utilized in the tribological investigation is the four-ball tribotester test machine. The results found that fatty acid inside vegetable oil can reduce the coefficient of friction and the flash temperature parameter. However, at the same time, the wear scar diameters and worn scar observations indicate that the surface of the metals is attacked by the chemical reaction of oxygen present inside the fatty acid chain of vegetable oil.